Optimal performance of an irreversible, heat engine-driven, combined vapor compression and absorption refrigerator - Göktun, Selahatti̇n (Elsevier BV, 1999)
By employing finite-time thermodynamic approach, the optimum performance of an irreversible heat engine-driven combined vapor compression and absorption refrigerator system is investigated. To get closer to real machines, the effects of thermal resistances and internal irreversibilities on the performance of the combined cycle is considered. The analysis show that the combined cycle has a significant increase in system performance over the heat engine-driven vapor-compression refrigerators.